Dreams and Nightmares in Patients With Obstructive Sleep Apnea: A Review - BaHammam, Ahmed S.; Almeneessier, Aljohara S. (Frontiers in Neurology, 2019)
Obstructive sleep apnea (OSA) can present with or provoke various psychological symptoms. In this article, we critically review studies that have examined dreams, dream recall, and dream contents in patients with OSA. Obstructive events induce recurrent sleep fragmentation and intermittent desaturations in patients with OSA, which may trigger different parasomnias, including nightmares. Contradictory results have been reported concerning dreams in patients with OSA; while some investigators have reported less dreams in OSA patients, others have described that patients with OSA have increased dreams with emotional content, mainly violent and hostile content. Although there are reports of respiratory-related dream contents in patients with OSA, most studies that have assessed the dream contents of patients with OSA revealed that respiratory-related dream contents were unusual. A clear association between post-traumatic stress disorders, comorbid OSA, and nightmares has been reported in several studies. Further, an improvement in nightmare frequency with continuous positive airway pressure (CPAP) treatment has been shown. An inverse relationship between the severity of OSA reflected by the apnea-hypopnea index and dream recall has been demonstrated in several studies. Future studies should differentiate between patients with non-stage specific OSA and patients with rapid eye movement (REM) predominant OSA.